Menangkal Paham Radikalisme Melalui Komunikasi Dua Arah pada Sekolah Islam dalam Perspektif Pendidikan Muslim Polity - Yanti, Novi; Reflianto, Reflianto (Proceedings of Annual Conference for Muslim Scholars, 2019)
The purpose of this article was to discuss the role of public relations to prevent radicalism through two-way communication at Islamic schools in the educational perspective of Muslim polity. Islamic schools in the implementation of public relations led by the head of publicist unit. It build a strategic of communication channel management of two-way communication model with the advantage of technological developments in the era of Industrial revolution 4.0. One of them is the management development strategy based on two-way digital communication and social media in an effort to ward off the radicalism at Islamic school. Construction of two-way communication is often dominated by two-way communication of the asymmetric model. This article revealed various research findings of the school public relation role in the Islamic education in building the two-way communication. The findings of this research study average showed a tendency of Islamic school more intensive build the asymmetric models of two-way communication, where the communication channel functioned more dominant for the promotion of Islamic school positive image than the counter of radicalism.. The transaction of communication in the relationship management in which oriented to strengthening, understanding, and awareness of all staff to compensate for the promotion of public relations with wish-fulfillment Islamic schools should also be balanced with the prevention of radicalism into the Islamic education. In this way, the transaction is expected in the new two-way communication that can run balanced and symmetrical as a theory Grunig